The Influence of Motorized Vehicle Tax Incentives on Regional Tax Revenue of West Java Province During the Covid-19 Pandemic - Rismawati, Rismawati (Maksi, 2022)
This research is to find out how much influence the motor vehicle tax incentive program has on the regional income of West Java Province during Covid-19. The sample of this research is as many as216 observational data during the motor vehicle tax incentive period from August to December 2021. The method used is descriptive and the verification method. Data processing using Eviews-12. The results of the research on the condition of vehicle taxes, the abolition of tax fines, the free transfer of motorized vehicle transfer fees and local tax revenues have increased. Motor vehicle tax, the abolition of motor vehicle tax fines and the free transfer of motor vehicle title fees had a significant effect on the direction of a positive relationship to regional tax revenues in West Java Province during the Covid-19 pandemic. Partially, motor vehicle tax, abolition of motor vehicle tax fines, free transfer of motor vehicle title fees during the Covid-19 pandemic had a significant effect on the direction of a positive relationship to regional taxes in West Java Province.